Queens of the age of chivalry : England's medieval queens. Book three, 1299-1409 - Weir, Alison, 1951- (Weir, Alison, 1951- England's medieval queens, 2022)
"Packed with dramatic true stories from one of European history's most romantic and turbulent eras, this epic narrative chronicles the five vividly rendered queens of the Plantagenet kings who ruled England between 1299 and 1399. The Age of Chivalry describes a period of medieval history dominated by the social, religious, and moral code of knighthood that prized noble deeds, military greatness and the game of courtly love between aristocratic men and women. It was also a period of high drama in English history, which included the toppling of two kings, the Hundred Years' War, the Black Death, and the Peasants' Revolt. Feudalism was breaking down, resulting in social and political turmoil. Against this dramatic backdrop, Alison Weir describes the lives and reigns of five queen consorts: Marguerite of France was seventeen when she became the second wife of sixty-year-old King Edward I. Isabella of France, later known as "the She Wolf," dethroned her husband Edward II and ruled England with her lover. In contrast, Philippa of Hainault was a popular queen to the deposed king's son, Edward III. Anne of Bohemia was queen to Richard II, but she died young and childless. Isabella of Valois became Richard's second wife when she was only six years old, but was caught up in events when he was violently overthrown. This was a turbulent and brutal age, despite its chivalric color and ethos, and it stands as a vivid backdrop to the extraordinary stories of these queens' lives"--